Linking Water Footprint with the Sustainable Development Goals: a Step-by-Step Method Description and Case Study - Menussi, Larissa Raquel Matias; Marques, Thamiris Linhares; Giusti, Gabriela; Silva, Daiane Vitória da; Figueirêdo, Maria Cléa Brito de; Silva, Diogo A. Lopes (Journal of Environmental Accounting and Management, 2026)
This paper calculated the water footprint (WF) of chilled chicken meat processing under alternative scenarios, including the contribution analysis to the Sustainable Development Goals (SDG). Volumetric WF was calculated according to the WF Network approach. The contribution of the system to the SDGs was analyzed using a qualitative screening approach. The results showed a WF of 136.1 liters for processing 1 kg of chilled chicken meat, with 0.7 liters from blue water and 135.4 liters from grey water. The wastewater treatment processes accounted for 99.5% of the total WF. According to scenarios analysis, to reduce the total WF of chilled chicken, it is necessary to invest in wastewater treatment technologies. The SDG analysis revealed potential positive contributions of the system to SDGs 2, 3, 6, 12, and 14 if the improvement scenarios are put in practice. The WF-SDG analysis was beneficial to evaluate the role of chicken meat processing in the search for SDGs, and to evaluate how the improvement opportunities can influence the system’s relationship to the SDG. The methodology for connecting the SDGs to environmental metrics can be replicated for any type organizations, enabling the integration of the SDGs in production chains. Connecting environmental metrics to the SDGs can indicate directions for production systems seeking sustainability improvements. Thus, it becomes beneficial for society’s search for 17 SDGs. There are few studies concerning WF and the SDGs, especially regarding industrialized products. Thus, this paper can contribute to this gap.